HUBUNGAN KEKUATAN OTOT LENGAN DENGAN KECEPATAN SERVIS PADA ATLET JUNIOR (Pendas : Jurnal Ilmiah Pendidikan Dasar, 2025)
This study aims to determine the relationship between arm muscle strength and service speed in junior athletes. The issue addressed is the persistent variation in service ability, which is suspected to be influenced by suboptimal arm muscle strength. This study used a quantitative correlational design involving junior athletes aged 13-17 years old selected through a purposive sampling technique. Arm muscle strength was measured using a dynamometer, while service speed was measured using a calibrated speed gun. Data analysis was performed using a Pearson correlation test to determine the relationship between the two variables. The results showed a positive and significant relationship between arm muscle strength and service speed, meaning that greater arm muscle strength, higher service speed. This finding underscores the importance of arm muscle strengthening exercises in improving service performance in junior athletes.